IMPLEMENTASI AKAD TABARRU’ DAN KONSISTENSI TATA KELOLA DANA DALAM INDUSTRI ASURANSI SYARIAH - Fitriah (Fakultas Syariah dan Ekonomi Islam Universitas Ibrahimy, 2026)
This study examines the implementation of the tabarru’ contract and the consistency of Tabarru’ Fund governance in the Islamic insurance industry using an integrative literature review approach. Normatively, the tabarru’ contract is positioned as a collective donation mechanism that underpins the principle of risk-sharing, yet various studies indicate that its operational application remains inconsistent. The findings reveal significant variations across companies in separating the Tabarru’ Fund from operational funds, managing contribution allocations, establishing technical reserves, and enforcing reporting transparency. These differences affect claim management quality and the formation of underwriting surplus, which many studies note still lacks standardized industry guidelines. Other influencing factors include the effectiveness of sharia governance, particularly the role of the Sharia Supervisory Board (SSB) and the readiness of sharia accounting infrastructure such as PSAK 108. This study highlights the need for a more integrative governance approach to strengthen the integrity of the risk-sharing mechanism in Islamic insurance.